Foundry properties of composites on AlMg10 alloy matrix with SiC and Cgr particles - C. Kolmasiak; M. Łagiewka (Metalurgija, 2023)
This paper presents the results of tests concerning the castability of metal composites based on an aluminium alloy matrix. The castability of composite suspensions containing carbide particles and suspensions containing graphite particles was tested using two tests: spiral and rod tests. It was found that as the volume fraction of particles increases, the castability of composites decreases, with graphite particles having a greater effect on the decrease in castability than silicon carbide particles. The paper also presents the results of research concerning the effect of ceramic particles on the shrinkage of solidifying and cooling composites. The shrinkage test results show a positive effect of ceramic particles introduced into the aluminium alloy, manifested by a decrease in the shrinkage value.